Faster, Sustainable and More Inclusive Growth An Approach to the Twelfth Five Year Plan (2012-17) - Planning Commission, Government of India (Planning Commission, Government of India, 2011)
The Indian economy on the eve of the Twelfth Plan is characterised by strong macro fundamentals and good performance over the Eleventh Plan period, though clouded by some slowdown in growth in the current year with continuing concern about inflation and a sudden increase in uncertainty about the global economy. The objective of the Eleventh Plan was faster and inclusive growth and the initiatives taken in the Eleventh Plan period have resulted in substantial progress towards both objectives. Inevitably, there are some weaknesses that need to be addressed and new challenges that need to be faced. Some of the challenges themselves emanate from the economy’s transition to a higher and more inclusive growth path, the structural changes that come with it and the expectations it generates. There are external challenges also arising from the fact that the global economic environment is much less favourable than it was at the start of the Eleventh Plan. These challenges call for renewed efforts on multiple fronts, learning from the experience gained, and keeping in mind global developments.
Government of India Planning Commission
Government of India Planning Commission
Keywords: Twelfth Five Year Plan- India